2009
DOI: 10.1016/s1877-1173(09)87002-6
|View full text |Cite
|
Sign up to set email alerts
|

Chapter 2 Progesterone Receptor Action in Leiomyoma and Endometrial Cancer

Abstract: Progesterone is a key hormone in the regulation of uterine function. In the normal physiological context, progesterone is primarily involved in remodeling of the endometrium and maintaining a quiescent myometrium. When pathologies of the uterus develop, specifically, endometrial cancer and uterine leiomyoma, response to progesterone is usually altered. Progesterone acts through mainly two isoforms of the progesterone receptor (PR), PRA and PRB which have been reported to exhibit different transcriptional activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 185 publications
(209 reference statements)
0
18
0
2
Order By: Relevance
“…Initially dubbed as "the progesterone hypothesis" (6), the role of progesterone in leiomyoma pathobiology is becoming more established (8,49). Kawaguchi and colleagues (50) demonstrated that mitotic activity in uterine leiomyomas is significantly higher in secretory (progesterone-dominant) phase compared with proliferative (estrogendominant) phase of the menstrual cycle.…”
Section: Progesteronementioning
confidence: 99%
“…Initially dubbed as "the progesterone hypothesis" (6), the role of progesterone in leiomyoma pathobiology is becoming more established (8,49). Kawaguchi and colleagues (50) demonstrated that mitotic activity in uterine leiomyomas is significantly higher in secretory (progesterone-dominant) phase compared with proliferative (estrogendominant) phase of the menstrual cycle.…”
Section: Progesteronementioning
confidence: 99%
“…The importance of P 4 has led to the continued development of synthetic progesterone receptor (PR) ligands for a variety of women’s health issues [1,2]. For example, oral contraceptives, combination hormone replacement therapy (HRT) for the treatment of menopausal symptoms, and to reduce the risk of endometrial hyperplasia and cancer associated with unopposed E 2 therapy [3-5].…”
Section: Introductionmentioning
confidence: 99%
“…Достоверные изменения экспрессии PR-B-изоформы рецептора прогестерона были выявлены лишь в Ki67-негативных лейомиомах, где было отмечено значительное усиление син-теза PR-B. Известно, что именно PR-B-изоформа рецептора прогестерона действует как актива-тор генов, ассоциированных с прогестероном, тогда как PR-A функционирует как ингиби-тор PR-B [11]. Точные механизмы, определяю-щие различную активность двух изоформ PR, полностью не установлены.…”
Section: Discussionunclassified
“…Точные механизмы, определяю-щие различную активность двух изоформ PR, полностью не установлены. Предполагают, что PR-A и PR-B имеют различную конформацию в клетке, что определяет их функциональные различия [11]. Так, PR-A-изоформа не способ-на эффективно рекрутировать коактиваторы рецепторов прогестерона SRc-1 и GRIP1 [12].…”
Section: Discussionunclassified